DNAR: Do Not Attempt Resuscitation - Kakkar, Kamna (Research and Humanities in Medical Education, 2020)
DNAR stands for ’Do Not Attempt Resuscitation’ which indicates that a person does not want to receive cardiopulmonary resuscitation or advanced medical care at the end of life when, in the specific case, the patient believes it may do more harm than good. I wrote this poem after one of my shifts in intensive care. Indian patients have the ’right to die with dignity’ - consensus guidelines were announced by ICMR in May, 2020. This is a historic milestone in the field of palliative medicine and end of life care.